Association of aspirin resistance with 4‐hydroxynonenal and its impact on recurrent cerebral infarction in patients with acute cerebral infarction - Guo, Juan (Brain Behav, 2020)
OBJECTIVES: To investigate the association of aspirin resistance (AR) with the plasma 4‐hydroxynonenal (4‐HNE) level and its impact on recurrent cerebral infarction (CI) in patients with acute cerebral infarction (ACI) who were receiving aspirin therapy. METHODS: One hundred and fifty‐four ACI patients who previously received aspirin therapy (100 mg/day) were enrolled. Whole urine (for measuring 11dhTXB2 and creatinine) along with blood (for measuring the plasma 4‐HNE level) were collected at least 7 days after the patients received aspirin. A cutoff of 1500 pg/mg of 11dhTXB2/ creatinine was used to determine AR. A follow‐up period to monitor recurrence CI events was 1 year. In addition, blood testing was performed when the patients were first admitted to hospital. RESULTS: Forty‐six of the 154 enrolled patients (29.9%) were found to be AR. No statistical difference in age, sex, hypertension, diabetes mellitus, coronary disease, smoking status, NIHSS score, TOAST classification, platelet count, thrombocytocrit, LDL‐C, HDL‐C, TG, and TC was found between the AR and aspirin‐sensitive (AS) patients, but the plasma 4‐HNE level was found to be higher in the AR patients than AS patients (p < .05). Multiple logistic regression analysis showed that the 4‐HNE level was associated with a higher risk of AR (OR = 1.034; 95% CI = 1.011–1.058; p < .05). Moreover, 1‐year follow‐up showed that AR was more prevalent in patients with recurrent CI (26 (56.6%)) than those without (20/(43.5%)) (p < .001). CONCLUSIONS: The plasma 4‐HNE level is strongly associated with AR and thus may be a factor contributing to AR. Patients with AR have a greater risk of recurrence CI.